Report of the Steering Committee Development of Human Resources for Health - Planning Commission (Planning Commission, 1997)
The nursing services in India has expanded considerably during the last 50 years. There is however, continued under-production of nursing manpower in India. As compared to developed countries the nurse population ratio in India is not satisfactory There is one nurse to 2198 people in India while in the developed countries the number of people served by one nurse ranged from 150 to 200. The earlier accepted recommendations envisaged a doctor nurse ratio of 1:3. This may not be applicable to the private sector specially general practice. In western countries there are 2 to 3 nurses to a doctor, the doctor nurse ratio was approximately 1:1.5 in India.
Government of India Planning Commission
Government of India Planning Commission